2019
DOI: 10.3390/ijms20030556
|View full text |Cite
|
Sign up to set email alerts
|

Class-3 Semaphorins and Their Receptors: Potent Multifunctional Modulators of Tumor Progression

Abstract: Semaphorins are the products of a large gene family containing 28 genes of which 21 are found in vertebrates. Class-3 semaphorins constitute a subfamily of seven vertebrate semaphorins which differ from the other vertebrate semaphorins in that they are the only secreted semaphorins and are distinguished from other semaphorins by the presence of a basic domain at their C termini. Class-3 semaphorins were initially characterized as axon guidance factors, but have subsequently been found to regulate immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 176 publications
6
84
0
1
Order By: Relevance
“…SEMA3D is found to inhibit tumour growth in colorectal and breast cancers, but it correlates with metastatic disease and worse survival in patients with pancreatic cancer [15,18,19]. SEMA3E shows tumour promoter role in multiple cancer types such as gastric, breast, and pancreatic cancers [11,12,[20][21][22]. In another study, both SEMA3D and SEMA3E was found to inhibit glioblastoma cell growth [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SEMA3D is found to inhibit tumour growth in colorectal and breast cancers, but it correlates with metastatic disease and worse survival in patients with pancreatic cancer [15,18,19]. SEMA3E shows tumour promoter role in multiple cancer types such as gastric, breast, and pancreatic cancers [11,12,[20][21][22]. In another study, both SEMA3D and SEMA3E was found to inhibit glioblastoma cell growth [23].…”
Section: Introductionmentioning
confidence: 99%
“…Class-3 semaphorins (SEMA3) are the only group of secreted proteins among the vertebrate semaphorins, and they are further sub-grouped into seven members (SEMA3A to SEMA3G). Similar to other semaphorin members, this family of genes has been reported to exhibit pivotal roles in a broad spectrum of biological processes, and recently their function in the regulation of immune system, angiogenesis, local cancer spread and metastases are becoming increasingly prominent [6][7][8][9][10][11][12]. Recent studies have shown that SEMA3s are secreted from tumour cells as well as from macrophages and fibroblasts, thereby influencing cancer cells and their microenvironments through direct or indirect mechanism to regulate cell-cell communications in the tumour micro-environment or vasculature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these proteins, namely leukemia inhibitory factor, CXCL1, trefoil factor 2, and the macrophage migration inhibitory factor are known to be involved in or encourage MSC‐mediated immunosuppression, which may subsequently enhance immune‐targeting by CM‐NGs as well. Additionally, the presence of semaphorin‐3C in the CM, a protein which is known to be involved in tumorigenesis through stromal support and which has specific receptors and influence on MSCs, could also partially explain the higher affinity of CM‐NGs towards cancer cells, at least in vitro …”
mentioning
confidence: 99%
“…Semaphorins were first identified as a family of genes encoding guidance molecules for the embryologic development of the nervous system [125,126]. The action mechanisms underlying semaphorins through their receptors from different cell types in different disease conditions had been summarized previously [127][128][129]. Cerani et al reported that neuron-derived Semaphorin3A is an early inducer of vascular permeability in diabetic retinopathy via neuropilin-1 [130].…”
Section: Neuron-derived Factors and Neovascularizationmentioning
confidence: 99%